Barriers to Medication Adherence Among Women Living in Rural Areas Suffering from Hypertension: The Case of Dikgale-Communities. (1st January 2016) - Shirindi, M.L.; Makhubele, J.C.; Fraeyman, J.
Abstract: Poor adherence to antihypertensive medications remains a significant challenge in the management of hypertension among women living in rural areas. The objective of the study was to assess the reasons of nonadherence in women suffering from hypertension. The researchers used a qualitative exploratory research design to conduct the study. A purposive sampling technique was used to select fifty (50) Black African women who participated in five (5) focus group interviews. The NVivo program was used to manage and organize the qualitative data. The study revealed that inadequate health literacy, financial constraints, forgetfulness and cultural differences are some of the barriers that prevent women from adhering to antihypertensive medication. Health promotion activities to empower women to become more proactive about their health needs and care should not be underestimated. As a result, they will be more likely to comply with their treatment, which will make them healthier in the long run.